2012
DOI: 10.1557/mrc.2012.11
|View full text |Cite
|
Sign up to set email alerts
|

Observations of unique plastic behavior in micro-pillars of an ultrafine-grained alloy

Abstract: When ultrafine-grained (UFG) samples are deformed plastically, it is necessary to consider the role of grain boundaries even at the micrometer scale in sample size. We report here the occurrence of intensive grain boundary sliding (GBS) at room temperature in micro-pillars of a UFG aluminum alloy having an unusually high strain rate sensitivity. A consequence of this GBS is that the intermittent flow with detrimental strain avalanches characterizing micro-sized conventional crystals is not present in UFG mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 13 publications
(28 reference statements)
3
28
0
Order By: Relevance
“…A similar effect was observed in an Al-30% Zn alloy in which coarse-grained samples exhibited avalanches in the load-displacement curves during micro-pillar compression while nanocrystalline samples exhibited stable deformation [43]. Thus, the compressed micro-pillars showed evidence of extreme slip in the coarsegrained samples while the nanocrystalline samples exhibited no slip traces but significant grain boundary sliding [43]. These earlier results are consistent with the present investigation where the appearance of the surface of a sample of magnesium processed by HPT and tested in tension, as shown in Fig.…”
Section: An Examination Of the Enhanced Ductilitysupporting
confidence: 67%
See 1 more Smart Citation
“…A similar effect was observed in an Al-30% Zn alloy in which coarse-grained samples exhibited avalanches in the load-displacement curves during micro-pillar compression while nanocrystalline samples exhibited stable deformation [43]. Thus, the compressed micro-pillars showed evidence of extreme slip in the coarsegrained samples while the nanocrystalline samples exhibited no slip traces but significant grain boundary sliding [43]. These earlier results are consistent with the present investigation where the appearance of the surface of a sample of magnesium processed by HPT and tested in tension, as shown in Fig.…”
Section: An Examination Of the Enhanced Ductilitysupporting
confidence: 67%
“…Furthermore, the micro-pillar surfaces showed evidence of bulges which might suggest an inhomogeneous strain distribution and a contribution to the deformation from grain boundary sliding. A similar effect was observed in an Al-30% Zn alloy in which coarse-grained samples exhibited avalanches in the load-displacement curves during micro-pillar compression while nanocrystalline samples exhibited stable deformation [43]. Thus, the compressed micro-pillars showed evidence of extreme slip in the coarsegrained samples while the nanocrystalline samples exhibited no slip traces but significant grain boundary sliding [43].…”
Section: An Examination Of the Enhanced Ductilitysupporting
confidence: 62%
“…[127] Micropillars of an Al-30% Zn alloy were prepared by HPT and FIB milling and tested in compression at room temperature within a depth-sensing ultra-hardness testing machine and this gave a high strain rate sensitivity and direct evidence for the occurrence of GBS. [128] In addition, these experiments showed that the strain avalanches that conventionally occur in the coarse-grained alloy during flow are absent in the UFG material.…”
Section: Observations On the Paradox Of Strength And Ductilitymentioning
confidence: 87%
“…Details of the pillar preparation were given earlier [3]. 3 The coherent domain size and the dislocation density in the HPT-processed disks were determined from analyses of X-ray diffraction line profiles measured by a high-resolution rotating anode diffractometer (type: RA-MultiMax9, manufacturer: Rigaku) using CuK 1 (wavelength  = 0.15406 nm) radiation.…”
Section: Experimental Materials and Proceduresmentioning
confidence: 99%
“…The best-known Al-Zn alloys, such as eutectic Al-95 wt.% Zn, eutectoid Al-78 wt.% Zn and solid solutions with Zn contents lower than 31.6 wt%, have been extensively studied [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%